The Effect of Human Development Index, Poverty Rate and Labor Force Participation Rate on Regency/City Economic Growth in South Kalimantan Province - Muhammad Riza Pahripi; Yunita Sopiana; Yuanita Setyastuti (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
South Kalimantan Province, a key contributor to Indonesia’s economy, faces disparities in economic growth driven by uneven human development, poverty, and labor dynamics. Despite abundant natural resources, regional inequalities persist, necessitating evidence-based policy interventions. This study analyzes (1) the partial and simultaneous effects of HDI, poverty rate, and TPAK on economic growth; (2) identifies the most influential variable; and (3) provides actionable recommendations for equitable development. Using panel data regression (2019–2023) and EViews 13, the study applies CEM, FEM, and REM models, validated by Chow, Hausman, and Lagrange Multiplier tests. Classical assumption tests (normality, multicollinearity, autocorrelation) ensure robustness. HDI and TPAK significantly boost economic growth, while poverty’s impact is statistically insignificant. HDI emerges as the dominant driver, underscoring the role of education, health, and income. Policymakers should prioritize HDI-enhancing investments (education, healthcare) and targeted poverty programs, particularly in high-disparity districts. Future research should expand variables (e.g., infrastructure) and timeframes for deeper insights.